EFEKTIVITAS PENGGUNAAN MEDIA VIDEO DAN ULAR TANGGA TERHADAP TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI SISWA KELAS XI - Faradina Lisanda Putri; Ika Yudianti; Herawati Mansyur (Poltekkes Kemenkes Malang, 2019)
High prevalence of adolescents reproductive health problems in Indonesia because of they have less knowledge. This study aims to measure the effectiveness of increased knowledge about reproductive health using video media and game snake ladders on grade XI high school 1 Dampit. This research uses the pre experimental design with two group post test only and the sample used in this study totaling 120 respondents using proportional random sampling. Students devided of videos group and snakes ladders group to give them reproductive health knowledge after that measure their knowledge level using questionnaire. Then count the results with U Mann Whitney test and the results showed that the mean rank score video media 66,93 and on media snake ladder 54,08. Conclusion of this research is the improvement of knowledge of reproductive health in adolescents using video more effectively then snakes ladders because students not only understand the lesson from listen what teachers speak but also from pictures was on video.